Загрози економічній безпеці України - Матвійчук, Наталія Миколаївна; Matviichuk, Nataliia M. (Східноєвропейський національний університет імені Лесі Українки, 2018)
Проаналізовано існуючі підходи до класифікації загроз енергетичній безпеці держави. На основі оцінки індикаторів енергетичної безпеки України виділено основні загрози національній безпеці держави в енергетичній сфері. Встановлено, що однією з вагомих загроз енергетичній безпеці України є значний рівень залежності від імпорту енергоносіїв, що несе ризики економічного та політичного впливу інших держав, залежність від світової кон’юнктури ринку. Виявлено тенденцію до поступової нейтралізації загроз енергетичній безпеці шляхом зменшення імпорту природного газу та диверсифікації поставок. Обгрунтовано, що постійний моніторинг загроз енергетичній безпеці є необхідним для захисту національних інтересів України, основою формування цілей та завдань енергетичної політики, вибору форм і методів забезпечення енергетичної безпеки.The existing approaches to the classification of threats to the country's energy security are analyzed by the place of origin (internal and external), by the factors of origin (objective, subjective), by the object of occurrence (relative to a certain type of energy resources), by the directions of origin (political, economic, social, environmental, etc.), by the sources of origin (natural, technogenic, anthropogenic), by the duration of action (single, short-term, medium-term, long-term), by scale of damage (minor, significant, catastrophic), by the nature of the impact on the energy sector (threats of direct and indirect impact), by the possibility of prediction (assumed and unpredictable), etc. The main threats to the national security of the state in the energy sector were identified based on the analysis of Ukraine's energy security indicators. It’s established that one of the major threats to Ukraine's energy security is a significant level of dependence on import of energy resources, which carries risks of economic and political influence from other countries, dependence on the world market situation. The tendency towards the gradual neutralization of threats to energy security by reducing the import of natural gas and diversifying supplies was found. The level of energy security in Ukraine is also negatively affected by the high level of the fixed assets’s deterioration on the fuel and energy enterprises, the reduction of the volume of capital investments in fuel and energy enterprises, the high level of energy intensity of GDP, the catastrophical indicator of losses during the transportation and distribution of energy, low share of renewable energy sources in energy balance, lack of effective structural reforms in the field of energy, efficient system of management of the energy sector, lack of effective control over the activities of natural monopolies, high level of negative impact of energy objects on the environment, inefficient system of subsidies for housing services, high energy prices and low income of the population, which cause high sensitivity to the growth of tariffs for housing services and the emergence of significant financial debt for electricity, heat supply and so on. It is substantiated that regular monitoring of threats to energy security is necessary to protect the national interests of Ukraine, the basis for the formation of goals and objectives of energy policy, the choice of forms and methods for ensuring energy security.
Threats to energy security in Ukraine
Keywords: енергетична безпека; energy security; загрози енергетичній безпеці; threats to energy security; індикатори енергетичної безпеки; indicators of energy security; енергоємність ВВП; energy intensity of GDP; енергоефективність; energy efficiency